THE IMPACT OF AUTONOMOUS LEARNING STRATEGIES ON LANGUAGE DEVELOPMENT (Eureka Journal of Language, Culture & Social Change, 2026)
This study examines how autonomous learning strategies affect the language development of Uzbek university students. In an experimental design, one group of first-year students received training and support in self-directed learning techniques while a control group followed traditional instruction. Language proficiency was measured before and after a semester-long intervention. The results indicate that students who engaged in autonomous learning activities showed significantly greater improvements in English proficiency than those in the teacher-directed control group. These findings suggest that fostering learner autonomy – through goal-setting, strategy training, and self-reflection – can substantially enhance language skill development. The study contributes real data from Uzbekistan’s context, addressing a gap in the literature, and supports educational reforms emphasizing student-centered and independent learning. Recommendations are offered for integrating autonomous learning strategies into language curricula to improve outcomes and promote lifelong learning skills. All data presented are authentic and reliable, with references provided for context and comparison.
Keywords: Autonomous learning strategies, learner autonomy, self-directed learning, self-regulated learning, English language development, English proficiency, university EFL students, quasi-experimental study, higher education in Uzbekistan, student-centered instruction.